175 Could COVID-19 Induced Endothelial Dysfunction Explain New Onset Peyronie's Disease?. Issue 1 (1st April 2022) - Rainer, Q.; Saltzman, R.; Premer, C.; Hurwitz, B.; Molina, M.; Ibrahim, E.; Hare, J.; Ramasamy, R.
ABSTRACT: Introduction: Coronavirus Disease 2019 (COVID-19) is an emerging infectious disease caused by a novel coronavirus (SARS-CoV-2) which has been found to cause systemic inflammation in some patients. Many possible long-term sequelae of COVID-19 have yet to be identified. Since endothelial cells have both angiotensin-converting enzyme 2 (ACE2) and transmembrane protease, serine 2 (TMPRSS2) receptors, and SARS-CoV-2 requires both receptors for cell entry, we hypothesized that widespread endothelial damage caused by COVID-19 infection leads to Peyronie's disease (PD). Objective: New-onset PD after resolved COVID-19 infection was evaluated. Methods: This study was performed after Institutional Review Board approval. After comprehensive history and physical exam, penile duplex was used to evaluate blood flow and characterize any plaques. International Index of Erectile Function (IIEF) was used to evaluate erectile function. Brachial artery flow-mediated dilation (FMD) and endothelial progenitor cell – colony forming units (EPC-CFU) assays were utilized as measures of endothelial function. Available data from two separate control groups were used for comparisons: "No PD" contains subjects with a history of cardiovascular disease and normal erectile function according to IIEF-EF score (n=27). This group was selected to serve as a negative control with endothelial dysfunction. A second control group "Healthy Controls" was selected as a positive control containing male participants who were free from any significant cardiovascular medical history (n=9). Results: New-onset PD after resolution of COVID-19 infection was identified in one patient. The penile duplex with erectogenic agents demonstrated normal vascular flow with presence of calcified plaques. The PD group median EPC-CFU levels were 0 as compared to 1.60 in the no PD (negative control) group and 20.00 in healthy (positive) controls. Similarly, median FMD% was impaired in the PD group (2.35%) and no PD group (3.88%) as compared to healthy controls (7.75%). Conclusions: These findings reveal a novel mechanism for PD after resolution of COVID-19 infection. These findings have significant clinical and biological implications for males with PD and should be considered as a possible sequela of COVID-19 infection. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: Acerus Pharmaceuticals, Boston Scientific, Coloplast, Endo Pharmaceuticals, Empower Pharmacy, Nestle Health, Olympus